Prevalence of cryptosporidium spp. infection among children admitted to hospital Tengku Ampuan Afzan - Abdullah, Asady; Ismail, Soraya, Marsitah; Pakeer, Oothuman (Malaysian Medical Association, 2019)
Introduction: Cryptosporidium spp. is identified as an important cause of diarrhoeal morbidity and mortality worldwide particularly in children below five years of age and immunocompromised individuals. Infections are present among cattle and humans. Until now, there is no report on its prevalence in humans in Kuantan. The aim of this study is to record the prevalence and associated risk factors of Cryptosporidium spp. infection among children admitted to Hospital Tengku Ampuan Afzan (HTAA), Kuantan. Methods: This is a cross-sectional study conducted among children admitted to the Paediatrics ward in HTAA between December 2017 and May 2018. Faecal samples were examined using wet smear and Modified Ziehl-Neelsen (MZN) staining techniques. Data on demography and hygiene practices was collected using a pretested questionnaire, and analysed using SPSS version 22. Results: One hundred thirty five children (95.6% were of Malay ethnicity) were included in the study. The overall prevalence of Cryptosporidium spp. infection was 25.2%. The prevalence was slightly higher in females (28.1%) than males (23.1%). The prevalence was higher than expected. This study showed that some risk factors namely children’s age and trash disposal methods were significantly associated with Cryptosporidium spp. infection (p˂0.05). Conclusion: Higher prevalence could possibly be due to an outbreak of this infection or until now undetected.